Pemberdayaan Anak-Anak Usia Dini Melalui Program Bimbingan Les Belajar Bahasa Inggris di Kampung Baru RT 01 di Desa Bantarsari - Zakki Munajih, Ahmad; Syamsul Abidin, Asad; Nurliani; Harun, Ernawati; Zulfikar Mumtaz, Ahmad; Hasan Muaziz, Muhamad (STIT Sirojul Falah Bogor, 2023)
This English tutoring programme is one form of community service programme (KKN-12 USA) in 2023 which aims to foster the ability of early childhood in learning English at Paud Insan Madani. In addition, there are other objectives, namely from the implementation of this programme, students can apply the knowledge and theories that have been obtained from the world of lectures, besides that the campus can show the community that students are able to reinforce the existence of universities that are able to create or give birth to the nation's successor cadres who are able to bring better changes to society. The target of this service is early childhood in Bantarsari Village RT 01 Rancabungur District, Bogor Regency. And this programme has the main objective, namely through the English tutoring programme, early childhood can get basic knowledge of English such as how to pronounce well and correctly, be it words or sentences used in daily activities related to their lives and ages. This tutoring programme lasts about 4 weeks with 2 meetings each on Friday and Saturday. From this programme it can be seen that before this activity the children did not understand anything about English and after this activity the children have a change in English language skills at a basic level.